Stage 2C of the CO2CRC Otway Project: Seismic Monitoring Operations and Preliminary Results. (July 2017) - Pevzner, R.; Urosevic, M.; Tertyshnikov, K.; Gurevich, B.; Shulakova, V.; Glubokovskikh, S.; Popik, D.; Correa, J.; Kepic, A.; Freifeld, B.; Robertson, M.; Wood, T.; et al.
Abstract: The CO2CRC's "Otway Stage 2C project" is a test injection of 15, 000 tons of supercritical gas mixture (80 mole% CO2 & 20 mole% CH4 ) at the CO2CRC Otway site in the Australian state of Victoria. The objective of this test is to examine the limits of surface seismic detection and to conduct detailed pressure monitoring of the injection. A key design feature of the project is injection near the bottom of a highly permeable formation, thereby allowing for buoyancy driven flow to thicken the plume and enhance seismic response. The project is specifically targeting observation of the development of the gas plume through a combination of multi-vintage 4D seismic surveys acquired with a buried seismic receiver array, 4D Vertical Seismic Profiling (VSP) and pressure measurements. Using both time-lapse seismic data and reservoir simulations, we aim to not only detect the plume but also demonstrate its eventual stabilisation. In this paper we discuss the technical aspects of the Otway Stage 2C seismic monitoring program and the initial results.